The fall of the Soviet Union: The fall of a state or the fall of an ideology - Sajjad Ali Khan (Journal of Political Studies, 2009)
During the last century or so, two dominant doctrines i.e. Capitalism and Socialism had been in a state of constant confrontation resulting in engaging the two Super powers, the United States and the Soviet Union in wars such as the Vietnam War and the Cold War. The Cold War that continued for several decades finally led to the disintegration of the Soviet Union. This article was an attempt to question the so called perception of conceiving socialism as a major cause of the disintegration of the USSR. It was found that the Russian Model of Socialism (Communism) was different from the Socialism of Marx and Engel in a number of aspects. It had also received immense criticism from some of the prominent Marxists. Based on the review of literature, the article concludes that the failure of communism in the Soviet Union should by no means be considered as the failure of socialism and as such socialism has nothing to do with the disintegration of the Soviet Union. Instead, it is in fact the special model of socialism adopted and implemented in the Soviet Union that led to its disintegration. The basic line of argument here is that the Russian socialism was completely at odds with the socialism of Marx and Engels both in its spirit as well as in practice.